Is ASEAN Ready for Banking Integration? Evidence from Interest Rate Convergence - Sahul Hamid, Fazelina; Lean, Hooi Hooi (UI Scholars Hub, 2016)
Convergence in prices or returns of assets with similar characteristics indicates that the financial market is integrated with regional markets. This paper is the first that test of the movements of interest rates in ASEAN banking sector for the period 1990 - 2012. The empirical analysis is based on a yearly panel of commercial bank interest rate data from 5 ASEAN countries, namely, Indonesia, Malaysia, Philippines, Singapore and Thailand. We assessed the degree and speed of interest rate convergence using beta and sigma convergence method. The findings show that the difference and the dispersion in the interbank rates have reduced since the Asian financial crisis and this trend has become stronger after the Global financial crisis. The findings of this study confirm that interest rates in the ASEAN banking sector are converging. This provides evidence that the ASEAN banking sector is ready for financial integration.